2010
DOI: 10.3390/en3061194
|View full text |Cite
|
Sign up to set email alerts
|

Residential Energy Performance Metrics

Abstract: Techniques for residential energy monitoring are an emerging field that is currently drawing significant attention. This paper is a description of the current efforts to monitor and compare the performance of three solar powered homes built at Missouri University of Science and Technology. The homes are outfitted with an array of sensors and a data logger system to measure and record electricity production, system energy use, internal home temperature and humidity, hot water production, and exterior ambient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The utility costs for residential consumers can be saved by the support of RESs and ESS [14] in smart grid architecture. The work presented in [15] outlined a detailed review of the current progression in the HEM system, challenges in appliance scheduling, and energy optimization in the smart grid community. In addition, the incorporation of RESs into households and their effects on utility tariffs have not been addressed properly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility costs for residential consumers can be saved by the support of RESs and ESS [14] in smart grid architecture. The work presented in [15] outlined a detailed review of the current progression in the HEM system, challenges in appliance scheduling, and energy optimization in the smart grid community. In addition, the incorporation of RESs into households and their effects on utility tariffs have not been addressed properly.…”
Section: Introductionmentioning
confidence: 99%
“…However, this work did not take into account the cluster-based energy management and energy allocation algorithm (EAA) in the smart grid framework. The authors in [15,16] demonstrated a household energy supervising system interfaced with a data logger unit to measure and record the electricity generation and demand patterns. In addition, RESs, ESS, and self-satisfied power demand were not considered to generate an alternative source of energy and storage facilities while peak demand appears.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors are involved when considering energy-saving designs, particularly for large-scale carbon-neutral community building developments; examples include the use of renewable energies [31], eco-designs [32], solar energy [33][34][35], lighting [36], compressed shopper waste (CSW) blocks [37], waste disposal [8], air-conditioning facilities [38], ventilation designs [39,40], shading designs [41], heating systems [42,43], green roofs [44], building envelopes [45], and wall insulation for buildings and double-skin facades [46][47][48]. Therefore, comprehensive preparation in integration and design is required to demonstrate effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the barriers, challenges, benefits, and future trends regarding the communication technologies and their role in the SG and SHs are also discussed. The authors in [14], demonstrate a residential energy monitoring system (REMS). Three SHs powered by an in-house RES (i.e., PV system) are considered for demonstration.…”
Section: Related Workmentioning
confidence: 99%